Dynamics of Telling Jokes in Plautus. The Case of the Self-Repair Routine - Berger, Łukasz (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The study concerns one recurrent type of conversational joke in Plautus, which consists of three different steps: (1) some problematic formulation by the joke-teller, (2) a request for an explanation by the interlocutor, and (3) a punchline. Using methods of Conversation Analysis, I interpret the routine as a case of a self-repair sequence and examine responses it triggers in all the comedies by Plautus. According to the quantitative part of the study, in half of the cases, humour is not acknowledged by the in-play recipient of the joke who may understand it literally or ignore it whatsoever. In the rest of the examples the joker’s interlocutor mostly reacts negatively (with some form of verbal aggression or complaint) or continues the non-serious mode of talking by launching another joke. Ultimately, the jocular routine is associated with the figure of rebellious slave, who uses the powerful joker’s position to tease and abuse the rules of a collaborative conversation.